Kompetensi Pendamping Simantri dalam Difusi Inovasi Teknologi Trichoderma pada Kelompok Tani Sri Uma Desa Takmung, Banjarangkan, Klungkung - TRI ADINDA HERPRASINTA DEWI; I DEWA PUTU OKA SUARDI; I KETUT SURYA DIARTA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2016)
Competence of the Companion Simantri during theTrichoderma Innovation Diffusion which Located in FarmersSri Uma, Takmung village, Banjarangkan, KlungkungAn integrated agricultural system (Simantri) is a breakthrough effort toaccelerate the adoption of agricultural technology because it is developed from apilot model in accelerating the transfer of technology to the rural communities.Since its introduction in 2009, there were Simantri which not able to improve thewelfare of Balinese people because of the lack of assistance. Problem that is oftenencountered as a companion attendant is the lack of competence of the attendant indiffusion process of the technological innovation. The aim of this study is todiscover the competence of the companion Simantri during the Trichodermainnovation diffusion which located in Farmers Sri Uma, Takmung village. Themethod used in this study is descriptive qualitative analysis method. The variableused in this study is a companion competence. The results showed that thecompetency of the companions in the diffusion of Trichoderma innovation isclassified in the excellent category, with a score of 86.68% from the maximumscore. The suggestion from this study is in addition to understanding thetechnological innovation that will be diffused, the companion must also understandthe capabilities of Simantri members since the differences in educational levels ofSimantri members.